Quantifying establishment limitations during the ecological restoration of species‐rich Nardus grassland. Issue 4 (30th August 2017) - Van Daele, Frederik; Wasof, Safaa; Demey, Andreas; Schelfhout, Stephanie; De Schrijver, An; Baeten, Lander; van Ruijven, Jasper; Mertens, Jan; Verheyen, Kris
Abstract: Aims: Successful establishment of species‐rich Nardus grasslands on ex‐agricultural land requires identification and removal of barriers to effective seed germination and seedling survival. Therefore, we investigate how germination and early development are affected by soil conditions from different restoration phases and how this relates to their specific plant strategies. Location: Grasslands and experiments in northern Belgium. Methods: We selected three grassland restoration phases ( Lolium perenne grasslands, grass–herb mix grasslands and species‐rich Nardus grasslands), which were characterized by a distinct plant community and soils with contrasting abiotic and biotic properties (respectively, eutrophic, mesotrophic and oligotrophic soils). In a first germination experiment we investigated the species‐specific responses (germination, lag time and emergence rate) of 70 grassland species (that typically occur along the restoration gradient) in each of the selected soils. Second, a mesocosm experiment was set‐up in which a mixture of 19 species (representative of the distinct grassland restoration phases) was grown together in the respective soils. Here, we analysed the intraspecific variation of plant growth, SLA and identified changes in community assembly. Results: Irrespective of soil influences, Nardus grassland species had significantly lower germination potentials and longer germination lag times than L. perenne grassland species. Germination (and its lag time) of grass–herb mix grassland species were negatively affected by the oligotrophic soils. Soil factors determined early growth patterns during the emergence and establishment phase. L. perenne grassland species exhibited a more plastic growth response and were highly dependent on soil type. Nardus grassland species exhibited large intraspecific variation in SLA, which was found to be significantly lower in the oligotrophic soils. Even though the difference in bio‐available P between mesotrophic and oligotrophic soils was minor, Nardus grassland species were only able to compete in the oligotrophic soils (no significant difference in biomass between communities). Mesotrophic mesocosms exhibited the highest species richness after 200 d of growth. Conclusion: Plant species from the three grassland restoration phases display distinct germination strategies, irrespective of soil type. Interactions between growth strategies and soil factors determine competitive asymmetry and therefore shape community assembly in the distinct grassland phases. Abstract : We investigated how soils from different restoration phases influence the distinct life phases and how this relates to their specific plant strategies. Plant species from three grassland restoration phases displayed distinct germination strategies, irrespective of the soil type. Interactions between growth strategies and soil factors determine competitive asymmetry and therefore shape community assembly in the distinct grassland phases.